ДЕЯКІ ПИТАННЯ ТЕХНОЛОГІЙ ПРОМИВАННЯ ТА КРІПЛЕННЯ СВЕРДЛОВИН У СКЛАДНИХ УМОВАХ - Ставичний, Євген; Ігнатов, Андрій (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2023)
Purpose. A thorough theoretical and laboratory study, as well as an analysis of the basic conditions for ensuring the reliability of the processes of washing and cementing boreholes in the presence of difficult geological and lithological conditions, using specific production data as an example, by developing and implementing innovative technical and technological techniques and methods. Methods. The study of well construction features in difficult conditions, in particular, the processes of flushing and cementing, was carried out using modern methods of analytical analysis and experimental studies using mathematical and physical modeling methods, modeling techniques and processing research results in the SolidWorks, STATGRAPHICS, MATHCAD environment, control and measuring instruments and related materials. Laboratory methods of control studied the technological characteristics of drilling fluids using special devices of the laboratory for monitoring the characteristics of cleaning agents, which are a working method for determining the characteristics of a hydraulic well washing program. The design of composite cementing material and stabilized buffer mixture was carried out using the method of orthogonal central-compositional planning, which makes it possible to reduce the number of experiments, streamline the search for optimal conditions, and obtain a mathematical model of the object of study. Findings. The main directions for improving technological methods and methods for the cycle of washing and cementing wells in complex geological and lithological conditions are outlined. As a priority direction for the development of well construction technology, methods for determining the formulations of high-quality flushing fluids, plugging systems, as well as designing a perfect technology for their application were chosen. The necessity of establishing the physical essence of the phenomena occurring during the implementation of well cleaning and casing technologies is substantiated, which in turn will allow determining the most rational parameters of well construction processes, that is, maximum productivity at minimum cost. A composite expanding cement mixture and a stabilized buffer mixture have been developed and studied, and using the method of orthogonal central compositional planning, the optimal amount of modifying additives in the composition of these systems has been determined. Originality. A necessary condition for the rational conduct of operations for flushing and cementing wells, during their construction in the thickness of sedimentary deposits, corresponds to certain, quite achievable technological parameters of the flushing and plugging systems used, as well as measures aimed at eliminating the shortcomings of the wellbore. Practical implications. The obtained results of laboratory and analytical studies, as well as the generalization of industrial and bench data are basic for designing the operating parameters of the process of flushing and plugging the casing string with guaranteed high technical and economic indicators. Data on the study of the features of well circulation processes and interaction with the wellbore of plugging systems are the initial ones for substantiating the design and technological parameters of the technical support of the well construction cycle.